Early growth response 1 (Egr-1) directly regulates GABA(A) receptor alpha 2, alpha 4, and theta subunits in the hippocampus - Mo, Jiwon; Kim, Chong-Hyun; Lee, Dongmin; Sun, Woong; Lee, Hyun Woo; Kim, Hyun (WILEY, 2015)
The homeostatic regulation of neuronal activity in glutamatergic and GABAergic synapses is critical for neural circuit development and synaptic plasticity. The induced expression of the transcription factor early growth response 1 (Egr-1) in neurons is tightly associated with many forms of neuronal activity, but the underlying target genes in the brain remained to be elucidated. This study uses a quantitative real-time PCR approach, in combination with in vivo chromatin immunoprecipitation, and reveals that GABA(A) receptor subunit, GABRA2 (alpha 2), GABRA4 (alpha 4), and GABRQ (theta) genes, are transcriptional targets of Egr-1. Transfection of a construct that over-expresses Egr-1 in neuroblastoma (Neuro2A) cells up-regulates the alpha 2, alpha 4, and theta subunits. Given that Egr-1 knockout mice display less GABRA2, GABRA4, and GRBRQ mRNA in the hippocampus, and that Egr-1 directly binds to their promoters and induces mRNA expression, the present findings support a role for Egr-1 as a major regulator for altered GABA(A) receptor composition in homeostatic plasticity, in a glutamatergic activity-dependent manner.
Keywords: IMMEDIATE-EARLY GENE; PROMOTER ACTIVITY; MESSENGER-RNA; RAT-BRAIN; C-FOS; EXPRESSION; STIMULATION; PLASTICITY; NEURONS; PHARMACOLOGY